2014
DOI: 10.1371/journal.pone.0096788
|View full text |Cite
|
Sign up to set email alerts
|

OTX2 Duplication Is Implicated in Hemifacial Microsomia

Abstract: Hemifacial microsomia (HFM) is the second most common facial anomaly after cleft lip and palate. The phenotype is highly variable and most cases are sporadic. We investigated the disorder in a large pedigree with five affected individuals spanning eight meioses. Whole-exome sequencing results indicated the absence of a pathogenic coding point mutation. A genome-wide survey of segmental variations identified a 1.3 Mb duplication of chromosome 14q22.3 in all affected individuals that was absent in more than 1000… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
51
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 62 publications
(64 reference statements)
4
51
0
Order By: Relevance
“…; Zielinski et al. ). While BMP4 and OTX2 are good candidates, we stress that further work is required to identify which specific genes affect variation in bill length.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…; Zielinski et al. ). While BMP4 and OTX2 are good candidates, we stress that further work is required to identify which specific genes affect variation in bill length.…”
Section: Discussionmentioning
confidence: 98%
“…BMP4 is a clear candidate for involvement in bill morphology, as studies in Darwin's finches, chickens, and ducks have experimentally demonstrated its role in beak development (Abzhanov et al 2004;Wu et al 2004). OTX2 plays a crucial role in craniofacial development across jawed vertebrates (Kimura et al 1997), and mutations in this gene and structural variants within the wider genomic region have been linked with craniofacial abnormalities in mice and humans (Hide et al 2002;Zielinski et al 2014). While BMP4 and OTX2 are good candidates, we stress that further work is required to identify which specific genes affect variation in bill length.…”
Section: Discussionmentioning
confidence: 99%
“…With the advent of next generation sequencing, there are increasing number of studies that have investigated subjects with CFM to identify the candidate risk variants. Notably, Zielinski et al investigated a large pedigree of five affected family members and identified a 1.3 Mb duplication of chromosome 14q22.3 implicating OTX2 as a candidate gene for hemifacial microsomia . A subsequent study identified a de novo missense variant in MYT1 gene (encoding the myelin transcription factor 1) in a patient severely affected with OAVS.…”
Section: Discussionmentioning
confidence: 99%
“…These include hemifacial microsomia (that is, facial asymmetry due to maxillary and mandibular hypoplasia and ear malformations), and the agnathia-otocephaly complex (AOC). [4][5][6][7] AOC (MIM#202650) is a rare, often sporadic, malformation complex of the first pharyngeal arch that is characterized by agnathia/dysgnathia, microstomia, aglossia/hypoglossia and variable displacement of the ears toward the midline. Prognosis is poor with affected individuals often dying shortly after birth due to respiratory failure secondary to airway obstruction.…”
mentioning
confidence: 99%
“…These are sparsely distributed throughout the gene and typically result in a protein product with reduced or no function. 1,4 All cases with OTX2-related disease reported to date were heterozygotes with 40% known to be de novo mutational events. Variable expressivity is common.…”
mentioning
confidence: 99%